FROM SILENCE TO STRENGTH: THE GENDERED SUBALTERN IN ANAND’S UNTOUCHABLE AND ADIGA’S THE WHITE TIGER - Singh, Vikram; Manisha; Ritu; Aman Deep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper deals with the issue of the gendered subaltern in Mulk Raj Anand’s Untouchable and Arvind Adiga’s The White Tiger. In Untouchable, Anand portrays the suffering of women especially at the hands of upper-caste Hindus through Sohini, who is tried to be raped by a Brahmin, Pandit Kali Nath in the temple courtyard. She also faces humiliation at the hands of other lower-caste women. Aravind Adiga portrays the suffering of women through two major female characters in his novel The White Tiger. Kusum, a poor and lower-class woman breaks the stereotypes of the Indian patriarchal system as she rules over all the members of the family, whether they are male or female. She makes all the important decisions and has all the financial power. Another character is Pinky Madam, who belongs to the higher class, a very firm and determined lady. She stands against the wrong and makes her life decisions.